(untitled) (Sebha University Conference Proceedings, 2024)
the transition temperature TC and its relationship to the energy gap 2∆ were determined. Moreover, the pseudo gap 2∆Ps and the binding energy of the electron pair 2∆pair were determined. The study showed that the energy gap of the compound LaO0.9F0.1FeAs was 2∆=7.62meV, and the pair binding energy The transition temperature TC and the energy gap 2∆ are considered the most important features of superconductors, and to improve the physical properties of these superconductors, focus is placed on these two features. In this research, the temperature dependence of heat capacity C(T) and resistance ρ(T) were modeled, through the transition from the normal state to the superconducting state, based on two basic concepts. The first is that the phonon mediates the electron pair as a bond between them, which is known as Cooper pairs, which are formed at the transition temperature, and the second is that electron pairs can exist with conduction electrons in the normal phase. Data for the compounds LaO1-xFxFeAs and SmO1-xFxFeAs were studied, and by applying the proposed model to these data and calculating the constants appearing in the my of the electrons was 2∆pair=0.358meV, while for the compound SmO0.9F0.1FeAs the results were 2∆=7.75meV and 2∆pair=0.36 meV. According to the proposed model, the compounds were classified as belonging to strong or weak coupling, where the 2Δ/kBTC=3.5-4.2 for the compounds LaO0.9F0.1FeAs and SmO0.87F0.13FeAs, which is consistent with the weak-coupling BCS gap ratio, while for the compounds SmO0.88F0.12FeAs and SmO0.9F0.1FeAs the 2Δ/kBTC >(3.5-4.2) and it belongs to the strong-coupling BCS gap ratio.